Visibility of Turkish amenities: Immigrant integration and social cohesion in Amsterdam - Sezer, Ceren (A+BE | Architecture and the Built Environment, 2020)
This chapter examines social and spatial characteristics immigrants’ commercial and communal amenities to understand the dynamics of their visibility on the street. It defines visibility as the observable physical features of immigrant amenities such as signs and practices, important for the integration of immigrant groups to the mainstream society. The research focuses on the visibility of Turkish immigrants in Amsterdam. For the social characteristics, it studies public and parochial realms that are established and maintained by these amenities. For spatial characteristics it examines these amenities at city level in terms of their location and at neighbourhood level in terms of their personalisation, permeability and robustness. The findings of this study indicate that visibility can be an operational concept to improve the amenities for the goals of integration.